Pemanfaatan Aplikasi E-Learning untuk Pembelajaran Materi Umum Berbasis Android - Widy Saeful Iman; Mei Lestari; Ni Wayan Parwati S (Universitas Indraprasta PGRI Jakarta, 2021)
E-learning application is one of the innovations used in learning. Learning with e-learning applications can provide flexibility in place and time for users. This research aims to develop an e-learning application as a learning medium called Teman belajar. In Teman belajar, there are two actors consisting of admin and users. Admin is an actor who manage all activities in Teman belajar. Users in this research can be divided into two functions, as an exercise maker and exercise seeker. The method used in developing Teman belajar uses the waterfall model. The result of test on Teman belajar in several different smartphones show that the resulting image quality or layout is good and there are no errors found, so it can be concluded that Teman belajar is going well as expected. With Teman belajar application, it hoped that it can fulfill user needs with various of general materials that can be selected as needed.